MULTICULTURAL EDUCATION IN THE LIGHT OF INTERNATIONAL ACADEMIC MOBILITY - Olha Svyrydiuk (Pavlo Tychyna Uman State Pedagogical University, 2017)
The article examines multicultural education in the light of international academic mobility be the example of Adam Mickiewicz University. The definitions of multicultural education and academic mobility are given in the article. Erasmus Mundus Project (Eminence I, Eminence II) goals are described. It is stated that Adam Mickiewicz University is one of the largest academic centers in Poland, which is playing a significant role in social, economic, and cultural transformations going on in Central-East Europe. It is outlined that implementation of multicultural education in AMU in the light of academic mobility is directly conducted through studying of specialized multicultural courses and indirectly through learning in multicultural groups, participation at summer schools, conferences, workshops etc. It is provided through courses such as «Multiculturalism and Tolerance», «Multicultural Societies and Multiculturalism as a Policy of the Post-Colonial Countries», «Introduction to Foreign Language Teaching and Learning», «Polish Language», and «Management of Tourism and Business. Introduction to Tourism Industry». The author stressed the role of multicultural group activity. It promotes intense and productive work, allows you to make decisions together in a group and identify the most significant moments in the work. Students learn how to work in a multicultural group, be able to solve tasks and achieve good results. The obtained experience promotes skills of intercultural communication with other cultures, understanding of the similarities between cultures and respect them. The author pays attention to extra-curricular work such as visiting museums, theatres, cinemas and sightseeing. Participating in summer school, conferences and workshop gives a nice possibility to meet new people from diverse cultural back-ground and build intercultural communication skills. The author summarizes that academic mobility contributes to the multi-cultural education development, giving real experience of being in a multicultural environment, develops intercultural skills, tolerant attitude to other people, acquaints with other cultures, and opens differences and similarities between cultures.